Rheological models of soil strata for the seismic microzoning of building sites - Kendzera, O. V.; Rushchitsky, J. J. (Reports of the National Academy of Sciences of Ukraine, 2016)
The features of applications of two basic rheological models of a geological environment – Kelvin–Voigt and standard – are considered for the analysis of vibrations in seismic-geological models of soil strata constructed according to the engineering-geotechnical surveys. An advantage of using the standard models that consists in the simple analytical description of seismic waves with the use of exact formulas and a fuller allowance for the creep and the stress relaxation is demonstrated.